2017
DOI: 10.1016/j.compositesa.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Friction of carbon tows and fine single fibres

Abstract: The aim of this study conducted on carbon tows and single fibres is to highlight some friction behaviours to help better understand the friction mechanisms that occur during the manufacture of carbon composites. These mechanisms are responsible for damage that reduces the specifications and lifetime of mechanical parts. An experiment has been developed in order to rub together two carbon tows, or two single carbon fibres (with a diameter down to 5 mm), at an angle of 90°. The influences of friction velocity, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 20 publications
4
19
0
Order By: Relevance
“…This graph highlights the good repeatability of the measurements for single fibres. This repeatability during a friction cycle was also proved in a previous study [26].…”
Section: Repeatability Of the Measurementsupporting
confidence: 49%
See 1 more Smart Citation
“…This graph highlights the good repeatability of the measurements for single fibres. This repeatability during a friction cycle was also proved in a previous study [26].…”
Section: Repeatability Of the Measurementsupporting
confidence: 49%
“…The experimental method and adjustments were described and argued elsewhere [26,27]. In fact, no other method has yet been proposed to measure the static and/or kinetic friction properties between single carbon fibres.…”
Section: Friction Experimentsmentioning
confidence: 99%
“…Results show consistent impact of the viscosity on both parameters. The tendency of the hysteresis behaviour towards a stationary state could originate from levelling phenomena on the contact interfaces and from the coating between the filaments as Tourlonias et al showed on single fibres [42]. The implications of these effects are also considered by Cao et al [25] during their shear behaviour benchmark study using the term 'mechanical conditioning'.…”
Section: Rheometer Bending Testsmentioning
confidence: 96%
“…In order to have a no penetration condition, the "hard contact" type is chosen. The friction coefficient introduced is µ = 0.05, which is often used for composite studies [22].…”
Section: Explicit Simulationmentioning
confidence: 99%